Older Patients and Patients with Severe Arteriosclerosis Are Less Likely to Develop Keloids and Hypertrophic Scars after Thoracic Midline Incision: A Survey-Based Analysis of 328 Cases. Issue 3 (6th July 2022) - Sugimoto, Atsuko; Ono, Shimpei; Usami, Satoshi; Nitta, Takashi; Ogawa, Rei
Abstract : Background: Surgery is a well-known trigger of keloid and hypertrophic scarring. Sternotomy scars are subject to high skin tension, which is known to promote pathologic scarring. This suggests that sternotomies in adults are associated with high pathologic scarring rates, which aligns with the authors' anecdotal experience. However, this notion has never been examined formally. Therefore, the authors conducted a survey-based cohort study of patients who had undergone a sternotomy. Methods: All consecutive Japanese adults (18 years of age or older) who underwent cardiovascular surgery with sternotomy in 2014 to 2017 were identified in 2019 by chart review and sent a questionnaire. Respondents formed the study cohort. The questionnaire presented randomly ordered photographs of representative mature, keloid, and hypertrophic scars and asked the patients to choose the image that best resembled their midline scar when it was particularly noticeable. The incidence of self-reported pathologic scarring (keloids and hypertrophic scars were grouped together) and the patient demographic (age and sex) and clinical characteristics (intima–media thickness of the left and right common and internal carotid arteries) that were associated with pathologic scarring were determined. Results: Of the 548 patients who underwent sternotomy, 328 responded for a 60 percent response rate. The mean patient age was 67 years, and 68.0 percent were male. Of these patients, 195 (59.5 percent) reported they had a pathologic scar. Compared with patients who had a mature scar, patients who had a pathologic scar had younger mean age (65 versus 69 years; p = 0.0002) and lower intima–media thickness (0.92 versus 1.05 mm; p = 0.028). Conclusions: Sternotomy was associated with a high rate of pathologic scarring. Older age and arteriosclerosis were associated with less pathologic scarring. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.